The process of converting to a near filmless operation at the University of Utah, Department of Radiology...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Freeh M; Baune D (Journal of Digital Imaging)
The Department of Radiology at the University of Utah Health Sciences Center has made the transition from a traditional film-based department to a near filmless operation. The University of Utah is a large teaching hospital and the transition from film in an educational facility will be discussed. This transition has had its difficulties and its success is dependent on the support of departmental leadership and hospital administration. We have had more than 100 years of experience with film, and current procedures were efficient given the limitations of the medium. While motivated by the traditional reasons for moving to a picture archival and communications system (PACS), such as film savings, unavailable films, and faster reports, we found the intangibles to be the larger issue, as well as a source for the largest benefits. This report will discuss the implementation process and the affect it had on all areas of the hospital, including its impact on hospital physicians, radiologists, file room personnel, and technologists. Procedure changes to the flow of patients, film, and electronic images will also be described. This process cannot be viewed as a one-time change, but must be viewed as a continuous process as areas of improvement are identified and new and improved technologies are developed. Copyright (c) 1999 by W.B. Saunders Company